Calcination of Clay Raw Materials in a Fluidized Bed - Kaczyńska, Katarzyna; Kaczyński, Konrad; Pełka, Piotr (Materials, 2021)
Clay raw materials are diverse in terms of their mineral composition, as well as the content of colouring oxides and their physical properties. Determining the suitability of raw materials for various purposes requires comprehensive studies on their properties, as well as their appropriate correction, which is possible through the use of appropriate modification techniques. One of the most commonly used technologies for the enrichment of clay raw materials is to subject them to high temperatures, which, depending on the temperature regime used in the technological process, may cause the decomposition and removal of some addditional components (e.g., carbonates), as well as the removal of water and dehydroxylation of clay minerals, reversible structural changes, and the complete and permanent reconstruction of the mineral phases. This paper presents a new application for fluidization technology in the calcination of clay raw materials. The results of the experiment show that the fluidization method is competitive compared to the technologies that have been used so far, as a result of, inter alia, the much shorter time period required to carry out the calcination process and, consequently, the much lower energy expenditure, the high efficiency of burning coal, and the lower CO2 emissions resulting from the mixing taking place in the reactor.